Floods of 18 and 19 November 2016 in Batouri (East Cameroon): Interpretation of the Hydro-Meteorological Parameters and Historical Context of the Post-Event Survey Episode - Paulin Sainclair Kouassy Kalédjé; Jules-Rémy Ndam Ngoupayou; Alain Fouépé Takounjou; Mireille Zebsa; Felaniaina Rakotondrabe; Joseph Mvondo Ondoa (The Scientific World Journal)
During the night of November 18 to 19, 2016, many stormy cells are not very mobile organized on the east of the southern plateau of Cameroon and dumped up to 260 mm of rain in 4 hours. Occurring on a relatively saturated soil, these rains caused strong floods of Kadey and Doumé. The floods were particularly damaging in the city of Batouri, where a subdivision was submerged by the Boumbé (tributary of the Sangha) with water heights in the houses reaching 1.75 m, despite the presence of a dam allowing clipping floods upstream of the basin. In this article, we present the results of the analysis of the postevent survey generated on this event with flow rates estimated on 15 sections of ungauged subbasins. These flows are then compared with those obtained from other recent postevent survey and those estimated by various regional estimations. The inventory of heavy rains around Batouri during the period 1970-2016 has led to the revision of current development standards in the region, which seem to underestimate rainfall and infrequent flows.